Chemical equilibrium of ion exchange in the binary mixture Cu2+ and Ca2+ in calcium alginate - da Silva, M. G. C.; Canevesi, R. L. S.; Welter, R. A.; Vieira, M. G. A.; da Silva, E. A. (Adsorption : journal of the International Adsorption Society, 2015)
Biopolymer alginate is capable of triggering interchain interactions in the presence of divalent and trivalent cations. Calcium alginate particles obtained by the emulsification method have been used in ion-exchange packed bed tests to remove synthetic copper effluents. Adsorption equilibrium data were obtained from single and binary component systems, which were subsequently subject to mathematical modeling. In the case of the modeling system with binary components, where the calcium was considered as a second ion, there was no significant improvement for the models analyzed, in counterpoise to the isotherm models applied to the single component system. The ideal law of mass action and the law of mass action which presupposed that both phases were non-ideal showed similar results. This process was found to be effective and feasible for industrial applications used to in heavy metal removal processes.